Maternal Outcomes associated with early preterm cesarean delivery - Kawakita, Tetsuya (Am J Obstet Gynecol, 2016)
BACKGROUND: Data on complications associated with classical cesarean delivery are conflicting. In extremely preterm cesarean delivery (22 0/7–27 6/7 weeks’ gestation), the lower uterine segment is thicker. It is plausible that the rates of maternal complications may not differ between classical and low transverse cesarean. OBJECTIVE: To compare maternal outcomes associated with classical comparing with low transverse cesarean after stratifying by gestation (23 0/7–27 6/7 and 28 0/7–31 6/7 weeks’ gestation). STUDY DESIGN: We conducted a multi-hospital retrospective cohort study of women undergoing cesarean delivery at 23 0/7–31 6/7 weeks’ gestation between 2005 and 2014. Composite maternal outcome (postpartum hemorrhage, transfusion, endometritis, sepsis, wound infection, deep venous thrombosis/pulmonary embolism, hysterectomy, respiratory complications, and Intensive Care Unit admission) was compared between classical and low transverse cesarean. Outcomes were calculated using multivariable logistic regression models yielding adjusted odds ratios with 95% confidence intervals and adjusted p-values controlling for maternal characteristics, emergency cesarean delivery, and comorbidities. Analyses were stratified by gestational age categories (23 0/7–27 6/7 and 28 0/7–31 6/7 weeks’ gestation). RESULTS: Of 902 women, 221(64%) and 91 (16%) underwent classical cesarean between 23 0/7 and 27 6/7 and between 28 0/7 and 31 6/7 weeks’ gestation, respectively. There was no increase in maternal complications for classical cesarean compared to low transverse cesarean between 23 0/7 and 27 6/7 weeks’ gestation. However, between 28 0/7 and 31 6/7 weeks’ gestation, classical cesarean was associated with increased risks of the composite maternal outcome (adjusted odds ratio=1.95; 95% confidence interval=1.10–3.45), transfusion (adjusted odds ratio=2.42; 95% confidence interval=1.06–5.52), endometritis (adjusted odds ratio=3.23; 95% confidence interval=1.02–10.21), and Intensive Care Unit admission (adjusted odds ratio=5.05; 95% confidence interval=1.37–18.52) compared to low transverse cesarean. CONCLUSION: Classical cesarean delivery compared with low transverse was associated with higher maternal complication rates between 28 0/7 and 31 6/7 weeks, but not between 23 0/7 and 27 6/7 weeks’ gestation.